Gambaran Involusi Pasar Kota (Suatu Tinjauan Etnoinformatika di Pasar Sugihwaras, Kota Pekalongan) - Nyarwi Ahmad; Rohman Rohman; Adam Wijoyo Sukarno (Badan Perencana Pembangunan, Riset dan Inovasi Kota Pekalongan, 2025)
The existing market and traders in Sugihwaras Market have provided an involutive reality. Three questions were formulated to understand and resolve the issue, namely (a) How is the existing condition of the involutive market, (b) Development and promotion strategies and (c) Resolution strategies. The ethnoinformatics method was applied to answer it with data excavated through five data collection techniques: (a) Qualitative survey, (b) Interview and Observation; (c) FGD; (d) Document study and (e) Visual study. Qualitative, quantitative data analysis and data triangulation have been carried out, in addition to interpretive, display, descriptive and frequency distribution (SPSS) techniques. The results of the study showed that the involutive reality was shown through the existing condition of the market which was quiet with buyers and traders, with hundreds of kiosks and traders closed and leaving. However, the market did not die but still survived with a small number of its traders. Various forms of training, partnerships and collaborations have been carried out to resolve it but the results have not been significant for the condition of the traders and the involutive market. Three options of resolution strategies are offered to get out of its involutive condition, namely: (a) a) Soft power; (b) Consistency and firmness in policy implementation; and (c) Adaptive culture. These three strategies are a unity of three in simultaneity (tri ning tri) so that all three must run simultaneously, filling and completing each other and not eliminating each other.